INFLUÊNCIA DOS MATERIAIS DAS VEDAÇÕES VERTICAIS NO DESEMPENHO TERMO-ENERGÉTICO DE UMA HABITAÇÃO DE INTERESSE SOCIAL - Almeida, Tatiane Pilar de; Brasileiro, Alice; Silvoso, Marcos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In 2009, Brazilian Federal Government launched the Minha Casa Minha Vida (MCMV) Program. However, it presented high standardized design solutions with similar constructive characteristics, regardless of the region in which they were located. The objective of this article is to analyze the influence of opaque materials used on vertical envelopment systems on the thermo-energetic performance of a multi-family social interest buildings. These are in the city of Rio de Janeiro, on the Bioclimatic Zone 8. Simulations were performed for different orientations, varying the selected opaque materials, considering the main constructive systems used by the Program. The performance of the building is evaluated through computer simulation, according to parameters defined by the Regulamento Técnico de Qualidade para o Nível de Eficiência Energética de Edificações Residenciais (RTQ-R). The worst results were obtained on the simulation using massive concrete as opaque material of the vertical envelopment, being, however, the construction system most frequently adopted by the program in Rio de Janeiro. The analysis showed the need to adapt the MCMV Program buildings using materials with better thermo-energetic performance on the vertical envelopments, due to the local climate.